Pelatihan Pembuatan Sabun Padat Eco Enzyme untuk Meningkatkan Keterampilan dan Kemandirian Ekonomi Masyarakat - Pratiwi, Diana Eka; Djangi, Muh. Jasri; Jumrah, Elfira; Putri, Suriati Eka; Perdana, Rini (Program Studi Manajemen FEB UNM, 2026)
The problem of household organic waste in Indonesia remains an environmental challenge that requires serious attention. Organic waste such as fruit and vegetable residues is generally not utilized optimally and is often disposed of directly, causing environmental pollution. One environmentally friendly effort to utilize organic waste is through the production of eco enzyme, which can be processed into economically valuable products such as solid soap. This community service activity aimed to improve the knowledge and skills of the community in Sapanang Village, Bungoro District, Pangkep Regency in producing eco enzyme-based solid soap while encouraging community economic independence. The implementation methods included socialization, education, hands-on practical training, mentoring, and evaluation. The results showed that participants demonstrated high enthusiasm during the training and were able to understand the process of making eco enzyme-based solid soap independently. In addition to increasing public awareness regarding the importance of organic waste management, this activity also created opportunities for home-based businesses using environmentally friendly products that have the potential to improve community income. Therefore, the eco enzyme-based solid soap training can serve as a form of community empowerment in supporting sustainable environmental management and improving the community’s economy